ALGORITHM FOR SEARCHING THE ATTRACTOR OF GENERAL VIEW DYNAMIC SYSTEM - A. Vejtsblit (Kherson State University, 2010)
In this article the effective algorithm allowing finding the attractor of any dynamic system in view of its irremovable casual fluctuations is represented.